New Advances in Semiconductors - Adriano Cavalheiro, Alberto (IntechOpen, 2022)
New Advances in Semiconductors brings together contributions from important researchers around the world on semiconductor materials and their applications. It includes seven chapters in two sections: "Calculations and Simulations in Semiconductors" and "Semiconductor Materials." The world will emerge different after the social and economic reorganizations caused by the COVID-19 pandemic and will be even more dependent on semiconductors than ever before. New Advances in Semiconductors is a book that brings together the contributions of important researchers around the world and is able to give an idea about the different characteristics of semiconductor materials and their applications. There is a section dedicated to theory, calculations and logic and another dedicated to the development and characterization of semiconductor materials of great future interest. I really hope that this book will help to spread knowledge about this research field to other researchers and students working in this area or even to those interested in starting their more advanced studies.